Business intelligence (bi) para a gestão orçamentária: um estudo de caso na fundação pti-br - Dzioba, Pamela Suelyn Passarini (2023)
Budget management is configured as a management tool to plan and control the financial resources of an organization. Its main objective is to support decision making, which often needs to be fast, considering the dynamic market environment. Allied to this purpose, among others, Business Intelligence (BI) tools have emerged to consolidate and transform data into secure, agile, and consistent information to assist, managerially, the different business processes. In view of this, the objective of this research was to describe the contributions that the likely implementation of a BI can bring to the budget management of the PTI-BR Foundation. The research methodology was characterized as descriptive and a qualitative case study, which used the protocol by Yin (2015). Also, two Systematic Literature Reviews were carried out for the theoretical foundation. The results showed as main contributions of the possible implementation, the reduction of effort of the team that conducts the budget management of the institution, as well as employees from other areas, the standardization and unification of data, reducing the use of different spreadsheets, easier and faster access, the reduction of transaction costs, the possibility of expanding the generation of budget information and consequently the subsidies for decision making, all delivered in an interactive format with a pleasant and dynamic design, thus raising the quality of delivery of budget information. Thus, it is indicated that the company proceed with the implementation and for this, an implementation project was proposed before the results of this research.